Perbandingan Hasil Atenuasi Tomografi 3D Menggunakan Metoda Spectral Fitting & Spectral Ratio Dalam Usaha Pemetaan Bawah Permukaan (Studi Kasus Gunung Guntur) - Awali Priyono; Gede Suantika; Sri Widiyantoro (Institut Teknologi Bandung, 2010)
Spectral fitting and spectral ratio methods are tested to estimate the Q value or attenuation in the effort on imaging the subsurface structure using three-dimensional tomographic inversion techniques. In this study, we used microearthquakes data around Mount Guntur that was collected from 1995 until 2007 that consist of 4800 seismograms. Analyses using the spectral fitting and spectral ratio methods generally depict the same anomalous areas. Studies using P and S waves indicate that the area of high attenuation corresponds to the area of low velocity that extending from mount Guntur to Kamojang caldera. In terms of the image quality, it can be seen that the attenuation derived using the spectral ratio of S wave has the same pattern with the one derived using P wave. This is due to the attenuation of S wave, which was derived directly from the P-wave. The Q value in the spectral ratio method depends on the width of the frequency window taken and the effect of noise in the determination the slope of the linear relationship between the natural logarithm of spectral ratio with frequency. The result of the spectral fitting analysis shows that the pattern of S wave attenuation image is different from the pattern inferred from the P wave data, because each attenuation image has been determined separately and does not depend on each other. Since the sensitivity of the values of Qp and Qs are important in fluid rock identification, the determination of Qs should not depend directly on Qp. With the various reasons above and more influential factor in estimating the value of Q using spectral ratio, the spectral fitting method is more recommendable to be employed to determine the value of Q.